2019
DOI: 10.1007/s10334-018-00732-0
|View full text |Cite
|
Sign up to set email alerts
|

A study of within-subject reliability of the brain’s default-mode network

Abstract: Objective Resting-state functional magnetic resonance imaging (fMRI) is promising for Alzheimer’s disease (AD). This study aimed to examine short-term reliability of the default-mode network (DMN), one of the main haemodynamic patterns of the brain. Materials and methods Using a 1.5 T Philips Achieva scanner, two consecutive resting-state fMRI runs were acquired on 69 healthy adults, 62 patients with mild cognitive impairment (MCI) due to AD, and 28 patients with AD dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 83 publications
1
7
0
Order By: Relevance
“…Resting-state fMRI images were preprocessed following an in-house procedure previously used by our team in published research (Postema et al, 2019). This initially included slice timing for synchronizing intra-volume temporal properties of slice acquisition and realignment for correcting volume-tovolume spatial displacement.…”
Section: Mri Processingmentioning
confidence: 99%
“…Resting-state fMRI images were preprocessed following an in-house procedure previously used by our team in published research (Postema et al, 2019). This initially included slice timing for synchronizing intra-volume temporal properties of slice acquisition and realignment for correcting volume-tovolume spatial displacement.…”
Section: Mri Processingmentioning
confidence: 99%
“…Changes in the frontal lobes, temporal lobes, and parietal lobes are variable and can be either increased or decreased (Kang et al, 2018 ). Some have suggested that a decrease in ALFF in the temporal region may be the result of neurotangles, which is a claim that cannot be denied (Postema et al, 2019 ). ReHo is a reliable rs-fMRI analysis algorithm to explore local functional connectivity (Li et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous prior studies have investigated the inter-day similarity in RS activity within a test-retest framework (Bijsterbosch et al 2017; Cox et al 2018; Noble et al 2019; Postema et al 2019). In that framework, the focus is on evaluating whether a particular measure of RS activity on day p was reliably reproduced for RS activity on day q in the assumed absence of a true change.…”
Section: Discussionmentioning
confidence: 99%